A necrópole romana do Eirô, Duas Igrejas (Penafiel): intervenção arqueológica de 2016 - Sousa, Laura (2020)
The (re)excavation, in 2016, by Penafiel's Municipal Museum, of one of the known parish's Roman necropolis at Eirô hamlet, was facilitated by the construction of the Duas Igrejas Parish Centre. In 1941, Abílio Miranda published the first news referring the casual finding of archeological burials in a ground between the church and the graveyard. Roman coarse wares and an ornamented ring were found there. These materials entered the Museum unrecorded. In this intervention the remaining grave structures of that occurrence were uncovered. Six more preserved inhumation tombs were partially or fully excavated that contained pottery, hobnails with fabric remains, and coins. It allowed for a new interpretation of the site and these burials datation, attributed to the 4th century A.D.